The Trickle Up Effect: Incorporating An Understanding of Immigration Law and Policies Into Best Interest Analysis in State Child Welfare Proceedings - Kathryn P. Banks (Washington University Global Studies Law Review, 2018)
Immigration law is an area of legal practice that requires an understanding of a complex, ever-changing landscape. With policies and laws widely changing, sometimes within the span of 280 characters, immigration attorneys have to be ready to address each crisis facing our nation’s broken immigration system. In the past eight weeks, the United States Supreme Court has decided that individuals being detained during deportation proceedings do not have the right to review of their detention status, and that parts of the Immigration and Nationality Act are unconstitutionally vague. Additionally, in Arizona, those enrolled in the Deferred Action for Child Arrival Program, are no longer eligible for in-state tuition for state educational institutions. Within this unworkable immigration system are undocumented children who face deportation proceedings, and a fight for their lives in a system that they do not know or understand. These are the children of whom Professor Estin speaks in her piece, Child Migrants and Child Welfare: Toward a Best Interests Approach. They are the shadow children.
Keywords: Child migrants; Child welfare; best interest; child immigrant; immigration